2021
DOI: 10.1113/jp281774
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent cold exposure improves glucose homeostasis despite exacerbating diet‐induced obesity in mice housed at thermoneutrality

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Importantly, it was recently demonstrated that BAT from obese mice, housed chronically at thermoneutrality closely resembles human BAT [4]. This model of 'physiologically humanised BAT' is now thought to represent the best choice for studying the physiology of this key metabolic tissue and it has recently been shown that intermittent cold exposure of thermoneutrally housed animals exacerbates diet-induced obesity [5]. Here, we extend this recent work by raising animals at thermoneutrality, on an obesogenic diet from weaning.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Importantly, it was recently demonstrated that BAT from obese mice, housed chronically at thermoneutrality closely resembles human BAT [4]. This model of 'physiologically humanised BAT' is now thought to represent the best choice for studying the physiology of this key metabolic tissue and it has recently been shown that intermittent cold exposure of thermoneutrally housed animals exacerbates diet-induced obesity [5]. Here, we extend this recent work by raising animals at thermoneutrality, on an obesogenic diet from weaning.…”
Section: Introductionmentioning
confidence: 69%
“…Rats are also more susceptible to weight gain, and fat accumulation when reared in the cold (18 • C vs. 30 • C), an effect which persists when housed at a common temperature [22]. More recently, it was demonstrated that ICE increases weight gain, largely due to increases in adiposity, in both male and female mice housed at thermoneutrality and fed a diet high in fat [5]. Despite no effect on circulating NEFA or insulin concentrations, ICE increased lipid deposition in hepatocytes and circulating leptin whilst decreasing circulating triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent issue of The Journal of Physiology , McKie et al . (2022) tested the effect on obesity of activating thermogenesis through repeated short bouts of cold exposure among physiologically ‘humanized’ mice. First, thermoneutral‐housed mice were fed either a low‐fat control or high‐fat diet to induce obesity.…”
Section: Translational Limitations In Rodent Studies Of Bat Thermogen...mentioning
confidence: 99%
“…Because the translational relevance for humans of such paradigms has been questioned, McKie et al . (2022) addressed this concern using an intermittent cold exposure (ICE) protocol, in which mice were briefly removed from thermoneutrality and placed for 1 h at 4°C, five times per week.…”
Section: Translational Limitations In Rodent Studies Of Bat Thermogen...mentioning
confidence: 99%
See 1 more Smart Citation